Ethical aspects of the Charter of the Fundamental Rights of the European Union. - Bompiani, Adriano (Medicina e Morale, 2002)
The European Council (EC), after the Nice summit held in December 27, 2000, has proposed to the European Parliament and to the Commission to solemnly proclaim, together with the Council, the "Charter of the Fundamental Rights of the European Union", elaborated by a Working Group in order to the order received in 1999 by the same Council. The document has a "political" value to endow the European Union (EU) of a more defined juridical and - under some aspects - "constitutional" basis, proposed for strengthening the consent of the European citizens of different countries that already belong to the EU and to direct those that would be part of it. The basis of unifying factors is substantially individualised in the "man's rights", historically developed respect to the man's individuality promotion and sociality during the XX century. The article resumes the examination of the recent national literature about the "Charter", but it dwells upon the rising bioethical aspects in the art. 1 (human dignity); art. 2 (right to the life); art. 3 (right to the integrity of the person). All these articles, announcing the "values" and consequent "rights", derive from the traditional juridical conception of the "person", from which can derive the insufficient protection of the prenatal phase of the human life. This can arouse worries and reserves forehead to a document that, for other aspects, it seems useful to allow an European development not limited to the mercantile aspects.